Interview with Wu Ming 1: QAnon, Collective Creativity, and the (Ab)uses of Enchantment. (December 2022) - Haiven, Max; Kingsmith, A.T.; Komporozos-Athanasiou, Aris
In this interview with Wu Ming 1, a member of the mysterious but well-known and widely-translated novel-writing Wu Ming Collective, we discuss his new book, La Q di Qomplotto ( The Q in Qonspiracy: How Conspiracy Fantasies Defend the System ). In the interview, Wu Ming 1 unravels the power of narrative and games in driving conspiracy fantasies and fuelling new forms of activism that have risen to confront a system that gives rise to them.